The rise of innovative credit scoring system in Indonesia: Assessing risks and policy challenges - Trissia Wijaya (Center for Indonesian Policy Studies (CIPS), 2023)
Strategies to monetize personal data have created opportunities for business innovation, including companies for credit ranking, marketing strategies, public health surveillance, and even penalty and reward mechanisms. Innovative credit scoring (ICS), which uses non-traditional personal data to estimate the creditworthiness of potential borrowers, is one such business innovation. There are about 19 ICS operators in Indonesia that help traditional and non-traditional lenders to estimate the capacity and willingness of potential borrowers to repay loans. Using non-traditional data to generate a credit score facilitates financial inclusion, especially for previously unbanked households. Despite this substantial benefit, the business model also carries inherent risks to data privacy, artificial intelligence and machine learning, and market monopolies. To address inherent risks in ICS, the Indonesian Financial Services Authority (OJK) as the regulator pursued a co-regulatory approach with the establishment of a regulatory sandbox. The Indonesian Fintech Association (AFTECH) also collaborates with OJK as the ICS umbrella organization. The self-regulatory function of AFTECH complements the supervision of fintech entities through the enforcement of a code of ethics among ICS operators. In addition, the Personal Data Protection Law (PDPL) aims to provide legal clarity for the personal data management of ICS companies.
Keywords: 330; Kreditwürdigkeit; Digitalisierung; Datenschutz; Finanzielle Inklusion; Indonesien